Importance of Feedback in Teaching English Language - O'ktamova Shaxrizoda Alisher qizi (Web of Journals Publishing, 2023)
The main goal of this academic article is to thoroughly examine the essential role of feedback in English language teaching. The investigation aims to delve into the significant impact of feedback on learners' acquisition and development of language skills. It specifically intends to analyze different feedback types and evaluate their effectiveness in promoting precise language usage. Additionally, the study aims to explore how these distinct feedback types contribute to improving learners' overall knowledge in English language classroom.
Keywords: feedback, linguistic competence, corrective feedback, content feedback, motivational feedback, error correction, building accuracy, monitoring progress.